Structure and diversity in a permanent plot of Melaleuca forest in rayong botanical garden, Thailand - Muenrew, Janjira; Panyadee, Prateep (Asian Health, Science and Technology Reports, 2020)
The aim of the study has been to describe the structural and floristic diversity of Melaleuca forest were studied over a 5-yr period at rayong botanical garden, Thailand. Methods structural (stem density, basal area) and floristic characteristics (composition, species diversity and morality rate). All trees > 14 cm DBH in a permanent plot of 100 m × 100 m (1 ha) were censured, in 2016 and 2020. Results, total of 2 trees (DBH ≥14 cm), 115 trees (DBH ≥14-30cm), 18 trees (DBH ≥30-50cm), 358 trees (DBH ≥50-100 cm) and 634 trees (DBH ≥100 cm) belonging to 4 species. The interval 5 years, there was a change of density, basal area and IVI. The species with the highest IVI value are Melaleuca quinquenervia (Cav.) S.T. Blake. (294.18=98.06 %) and diversity indices of Shannon-wiener index increased in 2020 (0.18). The forest structure consists of a two story tree layer and the top canopy height of 10 meters and means annual increment of 4.26 % per year. The soil characteristics are loam, sandy loam mixed with silt loam and strongly acid soils (pH 5.14).